Microwave‐assisted molecularly imprinted polymer synthesis for chemometric and rebinding mechanism of drug release applications - Vannessa, Lawai; Zainab, Ngaini; Saba, Farooq; Rafeah, Wahi; Showkat Ahmad, Bhawani (John Wiley & Sons Ltd, 2024)
Synthesis of molecularly imprinted polymers (MIP) has gained wide interest as drug delivery vehicles in recent years. The conventional one-variable-at-a-time method for determining the best formulation ratio of MIP templates is resource- and timeconsuming. Thus, this study focused on the response surface methodology optimization of the best formulation for MIP preparation using methacrylic acid and divinylbenzene as functional monomer and cross-linker, respectively. Two preparation systems were studied, namely microwave (MW)-assisted and conventional synthesis. The MIPs showed spherical particles with smaller particle sizes (500 nm–1.45 μm) and higher yields (0.5–1.2 g) via MW-assisted synthesis as compared to the conventional synthesis (size 660 nm–3.65 μm, yield 0.5–1.15 g). MW-assisted synthesis is faster and more efficient to synthesize controlled shapes and sizes of MIP particles. The rebinding properties of prepared MIP via MW were higher (7.15 ± 0.02 mg/g) than conventional synthesis (3.00 ± 0.31 mg/g). The empirical models were developed to correlate the output response of rebinding properties and input variables. The analysis of variance confirmed that experimental data were superbly fitted to the proposed response models. A satisfactory correlation between the experimental and predicted values was obtained by both MIP prepared via MWassisted and conventional synthesis.